Assessment of Prevalence and Factors Associated with Depression, Anxiety and Stress among Medical Students (Indian Journal of Public Health Research & Development, 2023)
Background: Medical students are challenged with academic, psychosocial, health factors which makes themeasily prone for Depression, Anxiety and Stress. The study aims to assess the prevalence of Depression, Anxietyand Stress among medical students and to identify the associated factors.Methods: A cross-sectional study involving all the medical students of ESIC Medical College, Kalaburagi who arewilling to participate. DASS 21 scale questionnaire was used to collect data.Results: The prevalence of Depression, Anxiety and Stress was found to be 17.75%, 29.91% and 12.13% respectively.Statistically significant association was found only between Stress and factors like gender and sleep hours.Conclusions: Medical students have notable amount of Depression, Anxiety and Stress which has to be addressedat individual level involving peers and family, ensuring endurance in all the activities.
Keywords: Anxiety, DASS 21, Depression, Medical students, Stress.